Association between depression and subjective cognitive complaints in 47 low- and middle-income countries. (October 2022) - Smith, Lee; Shin, Jae Il; Song, Tae-Jin; Underwood, Benjamin R.; Jacob, Louis; López Sánchez, Guillermo F.; Schuch, Felipe; Oh, Hans; Veronese, Nicola; Soysal, Pinar; Butler, Laurie; Barnett, Yvonne; et al.
Abstract: People with depression and subjective cognitive complaints (SCC) may be at particularly high risk for developing dementia. However, to date, studies on depression and SCC are limited mainly to single high-income countries. Thus, the aim of the present study was to investigate the association between depression and SCC in adults from low- and middle-income countries (LMICs). Cross-sectional, community-based data were analyzed from the World Health Survey. Two questions on subjective memory and learning complaints in the past 30 days were used to create a SCC scale ranging from 0 (No SCC) to 100 (worse SCC). ICD-10 Diagnostic Criteria for Research was used for the diagnosis of subsyndromal depression, brief depressive episode, and depressive episode. Multivariable linear regression was conducted to explore the associations. Data on 237, 952 individuals aged ≥18 years [mean (SD) age 38.4 (16.0) years; females 50.8%] were analyzed. After adjustment for potential confounders (age, sex, education, anxiety), compared to no depressive disorder, subsyndromal depression (b-coefficient 7.91; 95%CI = 5.63–10.18), brief depressive episode (b-coefficient 10.37; 95%CI = 8.95–11.78), and depressive episode (b-coefficient 13.57; 95%CI = 12.33–14.81) were significantly associated with higher mean SCC scores. The association was similar in all age groups (i.e., 18–44, 45–64, and ≥65 years), and both males and females. All depression types assessed were associated with worse SCC among adults in 47 LMICs. Future longitudinal studies are needed to investigate whether older people with depression and SCC are at higher risk for dementia onset in LMICs.